Analysing Teaching Strategy, Reflection and Networking Indicators Towards Learning for Sustainable Development (LSD) of Green Skills - Ramli, Syarina; Rasul, Mohamad Sattar; Mohd Affandi, Haryanti; Abd. Rauf, Rose Amnah; Pranita, Diaz (Journal of Technical Education and Training, 2021)
UNESCO-UNEVOC has reported that the levels of awareness towards the implementation of green skills amongst TVET teacher are at low level. Meanwhile, studies have shown that teacher have lack of skills and weak of knowledge about the concept of sustainable development. The study used quantitative approach and the structural equation model was used to measure the effect of the three indicators which are teaching strategy, networking, and reflecting towards learning of sustainable development. These indicators have been adapted from the Model of CSCT. The population of this study consisted of 202 TVET teacher trainee from the Institute of Teacher Education. Meanwhile the sample technique used is disproportionate stratified random sampling method and the sample size is 144. Findings show that networking and reflection were found to be positively related to learning for sustainable development, while teaching strategy was not significantly related to learning for sustainable development. The indicator of model was observed to be sufficiently solid and flexible to incorporate and measure the four construct which are cognitive, technology, emotional intelligence, and action competency. Finally, the results show that networking indicator have the strongest relationship to learning for sustainable development to develop green skills competency in industrial 4.0 amongst TVET teacher trainee.